Faktor Yang Berpengaruh Terhadap Niat Karyawan Melakukan Tindakan Whistleblowing Pada BCA KCP Ubud - I Gusti Agung Bayudha Arwata; Ni Wayan Rustiarini; Ni Putu Shinta Dewi (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
This examine objectives to decide the analysis of the factors that have an effect on the employee's intention to take whistleblowing at the BCA KCP Ubud financial institution. The pattern in this examine amounted to forty three human beings the use of general sampling approach or census. The evaluation method used is a couple of linear regression, evaluation the usage of SPSS. The effects confirmed that organizational dedication has a high quality effect at the goal to do whistleblowing, anonymous reporting channels have a fantastic impact on the intention to do whistleblowing, the extent of seriousness of the violation has a effective impact at the purpose to do whistleblowing. Private price does not affect the goal to take whistleblowing. Giving rewards has no impact on the aim to do whistleblowing.